The feasibility and methods of developing the foreign language teachers’ competence in the field of using digital technologies in professional activities - Vadim V. Grinshkun; Victoria V. Kopylova (RUDN Journal of Informatization in Education)
Problem statement. Every year, there are more and more studies aimed at improving the quality of digital resources created and used in the field of education, as well as at developing appropriate professional qualities among teachers. Within the framework of foreign language education, when using various digital tools, vocabulary is formed more effectively, dialogues are modeled, oral speech is used to a greater extent, and opportunities for mastering grammar are expanded. At the same time, existing research practically does not address the problem of finding integrated approaches to preparing teachers for the practical use of digital resources in the framework of the development of foreign language education. The problem of substantiating the expediency of improving the necessary systems for training teachers of a foreign language, searching for methods and means to improve the effectiveness of work with students of pedagogical specialties of universities is urgent. Methodology. A long-term study is being carried out, during which educational programs for bachelors and masters of pedagogical directions of metropolitan universities are being developed and improved. A series of experimental studies are being conducted to determine the effectiveness of the proposed developments. Results. The model, conditions, principles and content of training future foreign language teachers for the professional use of digital technologies are developed and described. An increase in several key parameters for the study was revealed, indicating the validity and effectiveness of the proposed approaches to the development of the studied competence of foreign language teachers. Conclusion. The implementation of approaches to the development of the competence of a foreign language teacher in the field of using digital technologies is appropriate. It is necessary to provide for the further development of methodological systems for teaching students at pedagogical universities the systematic use of such technologies not only in the context of teaching schoolchildren, but also in many other types of their professional activities.